Comparing the Performance of Organic Solvent Nanofiltration Membranes in Non‐Polar Solvents. Issue 9 (30th June 2021) - Merlet, Renaud; Winnubst, Louis; Nijmeijer, Arian; Amirilargani, Mohammad; Sudhölter, Ernst J. R.; de Smet, Louis C. P. M.; Salvador Cob, Sara; Vandezande, Pieter; Dorbec, Matthieu; Sluijter, Soraya; van Veen, Henk; VanDelft, Yvonne; et al.
Abstract: Organic solvent nanofiltration (OSN) is gradually expanding from academic research to industrial implementation. The need for membranes with low and sharp molecular weight cutoffs that are able to operate under aggressive OSN conditions is increasing. However, the lack of comparable and uniform performance data frustrates the screening and membrane selection for processes. Here, a collaboration is presented between several academic and industrial partners analyzing the separation performance of 10 different membranes using three model process mixtures. Membrane materials range from classic polymeric and thin film composites (TFCs) to hybrid ceramic types. The model solutions were chosen to mimic cases relevant to today's industrial use: relatively low molar mass solutes (330–550 Da) in n‐heptane, toluene, and anisole. Abstract : A variety of organic solvent nanofiltration membranes were screened and characterized for three industrial model cases. The influence of setups and membrane type on the results were statistically verified and commented.